If all banks have disclosed the information on their website how we will differentiate (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper examines the governmental policies and welfare programs at both the national and state levels in India that aim to provide assistance to elderly individuals. Given the growing number of aged individuals, it is crucial to prioritize the provision of a decent lifestyle for seniors. This research examines several efforts, assesses their efficacy, and proposes improvements.